Ghana’s Ashanti Pioneer Newspaper Aim High, Strive Hard, Go Forward - Hargrove, Jarvis L. (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
XIII, 238 p. 21 illus., 7 illus. in color.